2015
DOI: 10.1039/c5cp01874a
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Zn2+ ions into BaTiO3:Er3+/Yb3+ nanophosphor: an effective way to enhance upconversion, defect luminescence and temperature sensing

Abstract: Ferroelectric BaTiO3 became a multifunctional material via doping of lanthanide ions (0.3 mol% Er(3+)/3.0 mol% Yb(3+)) and subsequently upconversion luminescence was enhanced by incorporation of Zn(2+) ions. Upconversion luminescence of BaTiO3:Er(3+)/Yb(3+) perovskite nanophosphor has been studied using 800 and 980 nm laser excitations. The emission dynamics is studied with respect to its dependence on input power and external temperature including lifetime. Based on time-resolved spectroscopy, it is inferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(80 citation statements)
references
References 49 publications
4
75
1
Order By: Relevance
“…Compared with the square plate NaGd(MoO 4 ) 2 : 10% Yb 3+ /1% Er 3+ microcrystals synthesized as previously reported by us (temperature-dependent upconversion luminescence and thermometric sensitivity are shown in Supplementary Figs S9 and S10), the NaGd(MoO 4 ) 2 : 10% Yb 3+ /1% Er 3+ nanocrystals possess a more sensitive thermometric property. The maximum value of sensitivity of the NaGd(MoO 4 ) 2 : Yb 3+ /Er 3+ nanocrystals is 0.01333 K −1 at 285 K, which is higher than reported values of many other Yb 3+ /Er 3+ doped materials in a similar temperature range (around 300 K)2349505152535455.…”
Section: Resultscontrasting
confidence: 53%
“…Compared with the square plate NaGd(MoO 4 ) 2 : 10% Yb 3+ /1% Er 3+ microcrystals synthesized as previously reported by us (temperature-dependent upconversion luminescence and thermometric sensitivity are shown in Supplementary Figs S9 and S10), the NaGd(MoO 4 ) 2 : 10% Yb 3+ /1% Er 3+ nanocrystals possess a more sensitive thermometric property. The maximum value of sensitivity of the NaGd(MoO 4 ) 2 : Yb 3+ /Er 3+ nanocrystals is 0.01333 K −1 at 285 K, which is higher than reported values of many other Yb 3+ /Er 3+ doped materials in a similar temperature range (around 300 K)2349505152535455.…”
Section: Resultscontrasting
confidence: 53%
“…. Thus the temperature sensor developed in the present work has the highest thermal sensitivity compared to other materials918242627282930314142434445. If we compare the results of decay time, rise time and FIR studies of the present material then two different types of behavior of sensitivity is observed.…”
Section: Resultsmentioning
confidence: 76%
“…As the temperature increases the population of the 5 F 4 level (541 nm emitting band) increases and the fluorescence from this level increases gradually. The FIR technique uses the intensity ratio of two separate fluorescence wavelengths emitted from two closely spaced thermally coupled levels2425262728424344.…”
Section: Resultsmentioning
confidence: 99%
“…The (Y 0.968 Er 0.002 Yb 0.030 ) 2 O 3 particles have been synthesized through urea assisted combustion process [19]. This process has advantages over other usual techniques, e.g.…”
Section: Methodsmentioning
confidence: 99%